Hopf solitons and area-preserving diffeomorphisms of the sphere - Ferreira, L. A.; Razumov, A. V. (Kluwer Academic Publ, 2001)
We consider a (3+1)-dimensional local field theory defined on the sphere S-2. The model possesses exact soliton solutions with nontrivial Hopf topological charges and an infinite number of local conserved currents. We show that the Poisson bracket algebra of the corresponding charges is isomorphic to that of the area-preserving diffeomorphisms of the sphere S-2. We also show that the conserved currents under consideration are the Noether currents associated to the invariance of the Lagrangian under that infinite group of diffeomorphisms. We indicate possible generalizations of the model.
Keywords: solitons; Hopf topological charge; conserved currents; area-preserving diffeomorphisms